REBOP–FLAC3D hybrid approach to cave modelling - Fuenzalida, M.A.; Pierce, M.E.; Katsaga, T. (Caving 2018: Proceedings of the Fourth International Symposium on Block and Sublevel Caving, 2018)
The hybrid REBOP–FLAC3D approach allows prediction of the limits of the geomechanical zones defining the cave as a function of production. The results of the model can be used to derive estimates of: (i) caveability and caving rate, (ii) abutment stresses and cave loads, (iii) recovery and dilution entry, (iv) fragmentation, and (v) breakthrough timing and subsidence. The approach simulates the caving process by explicitly modelling each isolated movement zone derived from REBOP into FLAC3D to determine the yielded zone and cave back associated with mass drawn. After one cycle of extraction, REBOP informs the location of the movement zones and the presence of air, if it exists, to the continuum FLAC3D model. FLAC3D solves stresses associated with the presence of these zones and estimates the yielded zone surrounding the cave. FLAC3D informs REBOP which zones (initially inactive) could now be mobilised. The procedure is repeated until the draw schedule used as an input in REBOP is finished. Two of the main advantages of the hybrid approach include the capability of studying the potential impacts of isolated draw on cave growth and point loading on the extraction level, as well as the effect of including, explicitly, the airgap and mechanisms of fines migration and rilling on cave growth and subsidence. Two case studies are presented showing the capabilities of the hybrid approach.